Elections, Opportunism, Partisanship and Sovereign Ratings in Developing Countries - Vaaler, Paul M. (Institutional Knowledge at Singapore Management University, 2010)
We empirically examine whether and how opportunistic and partisan political business cycle (PBC) considerations explain election-period decisions by credit rating agencies (agencies) publishing developing country sovereign risk-ratings (ratings). Analyses of 391 agency ratings for 19 countries holding 39 presidential elections from 1987û2000, initially suggest that elections themselves prompt rating downgrades consistent with opportunistic PBC considerations, that incumbents are all likely to implement election-period policies detrimental to post-election creditworthiness. But more refined analyses, integrating both opportunistic and partisan PBC considerations in a unified framework, suggest that election-period agency downgrades (upgrades) are more likely as right-wing (left-wing) incumbents, become more vulnerable to ouster by challengers. Together, these results underscore the importance of integrating both opportunistic and partisan PBC considerations into any explanation of election-period risk assessments of agencies and, perhaps, other private, foreign-based financial actors important to the pricing and allocation of capital for lending and investment in the developing world. [ABSTRACT FROM AUTHOR]